2000
DOI: 10.1002/1099-0909(200007/09)6:3<178::aid-dys171>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

The reading comprehension abilities of dyslexic students in higher education

Abstract: The reading comprehension abilities of a group of dyslexic university students were compared with those of non-dyslexic university students. A 655-word passage, followed by literal and inferential questions, was used to measure reading comprehension. The text was designed to be syntactically complex, yet place relatively modest demands on decoding skills. Although dyslexic students performed at a similar level to the non-dyslexic students on the literal questions, their performance on the inferential questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 15 publications
11
57
0
7
Order By: Relevance
“…Describing dyslexia … [as a working memory deficit] … can help explain both the persisting writing language difficulties" (p. 16), as a rationale to explain why low working memory would cause problem in reading comprehension. This rationale is in agreement with Simmons and Singleton's (2000) view that the cause of inability to solve inferential problems (and thus dyslexia) is due to insufficient working memory capacity. Comprehension of text would certainly be undermined by insufficient capacity to buffer what was read before.…”
Section: Further Quotedsupporting
confidence: 86%
See 3 more Smart Citations
“…Describing dyslexia … [as a working memory deficit] … can help explain both the persisting writing language difficulties" (p. 16), as a rationale to explain why low working memory would cause problem in reading comprehension. This rationale is in agreement with Simmons and Singleton's (2000) view that the cause of inability to solve inferential problems (and thus dyslexia) is due to insufficient working memory capacity. Comprehension of text would certainly be undermined by insufficient capacity to buffer what was read before.…”
Section: Further Quotedsupporting
confidence: 86%
“…The term dyslexia refers to specific learning difficulty regarding written language (Jeffries and Everatt, 2004). Simmons and Singleton (2000) studied a group of dyslexic university students by comparing their reading comprehension ability with non-dyslexic students, and found that "dyslexic students were specifically impaired in constructing inferences when processing complex text" (p. 178). No difference was found between the dyslexic and non-dyslexic groups when literal questions, which only required information that was explicitly stated in the text, were given.…”
Section: Mapping Of the Felder-silverman Learning Style Model To The mentioning
confidence: 99%
See 2 more Smart Citations
“…the comprehension of people with dyslexia [47]. Similarly, Rello et al [44] demonstrate how text containing longs words were less understandable by people with dyslexia than the same texts when the long words were substituted by shorter synonyms.…”
Section: Readability In Target Populationsmentioning
confidence: 97%